1985
DOI: 10.1136/thx.40.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Smoking, allergy, and the differential white blood cell count.

Abstract: Dutch workers have proposed that people with asthma and those smokers who develop chronic airflow obstruction share a common allergic constitution. To study whether smoking itself is associated with indicators of allergy, we have examined 237 men aged [51][52][53][54][55][56][57][58][59][60][61] years (120 smokers, 73 ex-smokers, and 44 non-smokers) who were recruited to a long term study of lung function in 1974, at which time men with a clinical diagnosis of asthma were excluded. Smokers, ex-smokers, and non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
38
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(45 citation statements)
references
References 36 publications
6
38
1
Order By: Relevance
“…The lack of a relationship by speci®c allergy and pulmonary function has been reported [46,133,141]. However, all these investigators have used a grouped variable including one or more speci®c allergens and may thus have obscured any signi®cant relationship between speci®c allergy and reduced lung function level.…”
Section: Skin Prick Test: Relationship To Sex Age Ethnic Group Envmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of a relationship by speci®c allergy and pulmonary function has been reported [46,133,141]. However, all these investigators have used a grouped variable including one or more speci®c allergens and may thus have obscured any signi®cant relationship between speci®c allergy and reduced lung function level.…”
Section: Skin Prick Test: Relationship To Sex Age Ethnic Group Envmentioning
confidence: 99%
“…Conversely, TAYLOR et al [46], in a study concerning the association between smoking itself and indicators of allergy, reported lower values of the percentage of eosinophils, 1.67% in nonsmokers and 1.95% in smokers.…”
Section: Prevalence In Epidemiological Studiesmentioning
confidence: 99%
“…CS-AEP patients may also develop eosinophilia during the recovery stage, which has been reported in this issue (13). Although some investigators have reported a relationship between cigarette smoking and eosinophilia (15)(16)(17)(18)(19), it is not well knownthat cigarette smokecan induce acute eosinophilia. In 1999, we reported the apparent first reported case of cigarette smoke-induced acute eosinophilia (sudden elevation of peripheral eosinophils within a week) (14).…”
mentioning
confidence: 92%
“…Mediators like major basic protein (MBP), eosinophil cationic protein (ECP), and eosinophil peroxidase (EPO) takes active role in smokers [39]. Taylor and coworkers also reported the same [40]. Psychological stress and grief decrease the lymphocyte count [41].…”
Section: Stress Related Alteration In Stai Scores and Role Of Differementioning
confidence: 68%